2016
DOI: 10.35790/ecl.4.2.2016.14346
|View full text |Cite
|
Sign up to set email alerts
|

Angka kejadian afasia pada stroke di Instalasi Rehabilitasi Medik RSUP Prof. Dr. R. D. Kandou Manado tahun 2015

Abstract: Aphasia is a general term used to define a set of language disorder that occurs after brain damage commonly in the left hemisphere. The most underlying etiology of aphasia is cerebrovascular disease, stroke. Aphasia is present in 21-38% of patients with acute stroke and its impact is associated with short-term and long-term morbidity, high mortality rates, and limitations of the patients socialization. So as to raise awareness of disability caused by stroke, especially aphasia, it is necessary to know the inci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
1
5

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 0 publications
1
4
1
5
Order By: Relevance
“…In this study, the majority of post-stroke patients were 41-65 years old and thus categorized into middle adulthood. These results differ from the research of Purnomo et al (2016), who found that the majority of 455 stroke patients (212 patients) were aged 60 years. Age is a risk factor of stroke i.e., the incidence of stroke increases with age.…”
Section: Discussioncontrasting
confidence: 99%
“…In this study, the majority of post-stroke patients were 41-65 years old and thus categorized into middle adulthood. These results differ from the research of Purnomo et al (2016), who found that the majority of 455 stroke patients (212 patients) were aged 60 years. Age is a risk factor of stroke i.e., the incidence of stroke increases with age.…”
Section: Discussioncontrasting
confidence: 99%
“…5 Penelitian menunjukkan angka kejadian afasia pada stroke yang cukup tinggi, yaitu 13-40%. [6][7][8] Pemulihan afasia dapat terjadi secara bertahap dalam beberapa bulan pertama pascastroke. Menurut Watilla dkk pemulihan afasia sulit diprediksi karena banyak faktor yang memengaruhi proses pemulihan tersebut.…”
Section: Pendahuluanunclassified
“…Hal ini sesuai dengan data dalam penelitian lain yang menunjukkan angka kejadian afasia pada stroke 13-40%. [6][7][8] Sindrom afasia terbanyak pada stroke fase akut penelitian ini adalah afasia global diikuti afasia Broca. Bohra dkk pada tahun 2015 juga mendapatkan sindrom afasia terbanyak yaitu afasia global diikuti afasia Broca.…”
Section: Pembahasanunclassified
“…UK Stroke A ssociation (2016) menyatakan 33% dari pasien stroke mengalami afasia. Penelitian di Manado menyebutkan dari 455 pasien stroke, 13,2% mengalami afasia dan banyak terjadi pada usia diatas 60 tahun (40%) serta terjadi pada kasus stroke non hemoragik (60%) (Purnomo, Damopolii, & Sengkey, 2016).…”
Section: Pendahuluanunclassified